Analisis Implementasi Kurikulum Merdeka pada Sekolah Penggerak di SDN 1 Selorejo Kecamatan Dau Kabupaten Malang - Dewi, Radeni Sukma Indra; Suciptaningsih, Oktaviani Adhi; Anggraini, Ade Eka; Kusumaningrum, Shirly Rizki; Mudrikah, Mudrikah (Universitas Nusantara PGRI Kediri, 2023)
The Independent Curriculum is an intracurricular curriculum in which the material is maximized so that students have more time to develop learning ideas and expand their competency. The Mobilizing School's role in implementing the Independent Curriculum is to create an operational curriculum that satisfies the learning requirements of students. Schools also provide infrastructure and human resources to facilitate the Independent Curriculum's implementation. In this study, a qualitative descriptive approach was used to describe the topic about the circumstances and information gathered during the observation, as well as the challenges encountered, so that it became valuable knowledge and input to policymakers in revising the curriculum. The findings of this study reveal that the Independent Curriculum has been implemented maximally and stably in Mobilizing Schools, albeit there are still numerous inadequacies and challenges to its implementation. The ability of school leaders and teachers to implement changes is critical in the implementation of the Independent Curriculum in Mobilizing Schools. The principle, as a leader and facilitator, must be able to influence the mentality of the human data source staff in order to carry out reforms at the school and ensure that the Independent Curriculum is implemented efficiently.